Spodoptera frugiperda: response of different populations to the Cry1Ab toxin - ZENNER DE POLANÍA, INGEBORG; MALDONADO, HELBER ADRIANARÉVALO; MEJÍA-CRUZ, RODOLFO; DÍAZ SÁNCHEZ, JULIÁN L. (Revista Colombiana de Entomología, 2009)
Spodoptera frugiperda is the insect pest that causes the highest losses to corn production in the Tropics and Neotropics. Its control in Colombia accounts for at least 10% of production costs. Transgenic plants with the Cry1Ab toxin are proposed to decrease losses and avoid the use of insecticides. In order to manage possible resistance to the toxin and to monitor the phenomenon inherent in this insect, studies should be conducted on its baseline susceptibility and on larval behavior on transformed plants. The objective of this research was to establish the baseline for different populations, feeding neonate larvae with a meridic diet with a serial dosage of incorporated toxin to monitor the susceptibility of larvae to Cry1Ab through time. In addition, the effect of the consumption of tissue from the transgenic hybrid by larvae was determined. The baseline calculated for the zone of Tolima corresponded to 5.64ppm, while that of the coffee growing zone of Cundinamarca was 8.35ppm. Through time the Tolima population decreased its susceptibility, while that of Cundinamarca, not subjected to selection pressure did not vary considerably. Neonate larvae suffered 96.66% mortality when fed fresh tissue, green foliage of the transgenic hybrid, while those fed with yellow foliage showed a mortality of 76.59%. It was concluded that the fall armyworm shows a marked tendency to acquire tolerance to Cry1Ab within a short time.